1995
DOI: 10.1007/bf00371740
|View full text |Cite
|
Sign up to set email alerts
|

Lack of selectivity of protoporphyrin IX fluorescence for basal cell carcinoma after topical application of 5-aminolevulinic acid: implications for photodynamic treatment

Abstract: Clinical trials of topical ALA in photodynamic therapy (PDT) of basal cell carcinoma (BCC) show significant recurrence rates. Exogenous 5-aminolevulinic acid (ALA) is converted by intracellular enzymes to photoactive protoporphyrin IX (PpIX) in human tissues. PpIX generates cytotoxic singlet oxygen when irradiated with visible light in the 400-640 nm range. To evaluate variability and heterogeneity in PpIX production by tumors in such trials, and to assess the usefulness of PpIX for marking skin tumors, we mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…This can be explained by the increased uptake of MAL by the abnormal tissue. This occurs due to the cell changes in BCC as suggested by Martin et al [13]. Differences in the PpIX intensity may also be due to cell type from different tissues as observed by Inada et al [25].…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…This can be explained by the increased uptake of MAL by the abnormal tissue. This occurs due to the cell changes in BCC as suggested by Martin et al [13]. Differences in the PpIX intensity may also be due to cell type from different tissues as observed by Inada et al [25].…”
Section: Discussionmentioning
confidence: 83%
“…This is possible because the photosensitizer molecules have higher affinity to cancer cells compared to normal cells. It has been shown widely in preclinical and clinical studies that PS fluorescence can be useful contrast for improved visualization of cancer region and help surgeons delineating tumor margins during surgical resections [11][12][13].By using 5-aminolevulinic acid (ALA) or the methyl aminolevulinate (MAL) as precursor of protoporphyrin IX (PpIX), it is possible to use fluorescence to quantify PpIX content at pre-and post-treatment [6,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The inflammatory process occurring after seven days following the first PDT session is observed in Figure 1, panel B, which is characterized by enhanced expression of pro-inflammatory cytokines and leukocyte infiltration [16]. Many studies on the efficacy of PDT on BCC have been published [4,17,18]. However, only few studies have reported on the topical application of PDT for the treatment of BCC of eyelid cancer [19,20].…”
Section: Discussionmentioning
confidence: 99%